A facile one-step synthesized epsilon-MnO2 nanoflowers for effective removal of lead ions from wastewater. (July 2020) - Lin, Mei; Chen, Zuliang
Abstract: The increasing contamination of lead ions (Pb(II)) in groundwater has become a serious environmental issue, which provides the impetus for intense research on Pb(II) removal. ε-MnO2 nanoflowers were successfully fabricated through a simple decomposition reaction. And the obtained ε-MnO2 nanoflowers were employed to remove Pb(II) from water. The detailed microstructure and surface properties of ε-MnO2 were systematically characterized. The results indicate that the pure ε-MnO2 phase was obtained and the specific surface area is 96.33 m 2  g −1 . Batch adsorption experiments of Pb(II) were carried out, and the ε-MnO2 nanoflowers exhibited outstanding adsorption performance. The maximum adsorption capacity for Pb(II) and Cd(II) achieved to 239.7 mg g −1 and 73.6 mg g −1 at the dosage of 0.2 g L −1 . Besides, the prepared ε-MnO2 nanoflowers show much higher removal efficiency toward Pb(II) compared with commercial MnO2 . The XRD results reveal the stability of ε-MnO2 nanoflowers, and the XPS results suggest that both the electrostatic interaction and structural tunnels are responsible for the removal mechanisms of Pb(II). This work finds a facile method to synthesize ε-MnO2 nanoflowers, showing great potential for Pb(II) removal. Graphical abstract: Image 10 Highlights: ε-MnO2 nanoflowers were successfully fabricated by a simple decomposition. ε-MnO2 nanoflowers were employed to remove Pb(II) from water. The maximum adsorption capacity for Pb(II) achieved to 239.7 mg/g. Removal mechanisms was based on electrostatic interaction and structural tunnels.